How Do Vanadium Chloroperoxidases Generate Hypochlorite From Hydrogen Peroxide And Chloride? A Computational Study - Muhammad Qadri Effendy Mubarak; Emilie F. Gérard; Christopher F. Blanford; Sam Hay; Sam P. de Visser (American Chemical Society, 2024)
Indexed by ERA